Dermocosmetic Bioactive: Safety Assessment and Regulatory Challenges - Akram, Afifa; Gaur, Radhakrishan; Singh, Indu; Chauhan, Shikha Baghel (Current Drug Safety, 2025)
<span class=
Keywords: skincare